It all begins with a seed - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Good quality seeds are essential to successful vegetable production. This book focuses on the continuing interest and activities related to vegetable seed production programmes.Vegetable Seed Production (second edition). R A T George. CABI. 1999....